2015
DOI: 10.4252/wjsc.v7.i6.945
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the epigenetic control of satellite cells

Abstract: Epigenetics finely tunes gene expression at a functional level without modifying the DNA sequence, thereby contributing to the complexity of genomic regulation. Satellite cells (SCs) are adult muscle stem cells that are important for skeletal post-natal muscle growth, homeostasis and repair. The understanding of the epigenome of SCs at different stages and of the multiple layers of the post-transcriptional regulation of gene expression is constantly expanding. Dynamic interactions between different epigenetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 109 publications
0
27
0
3
Order By: Relevance
“…Among several epigenetic mechanisms, the role of microRNAs in muscle development and myogenesis has been most widely studied in the last decade. MicroRNAs are small, regulatory, non-coding RNA molecules that are mostly located within the cells, although they may also be identified in biological fluids and cell culture media (25). MicroRNAs regulate gene transcription by either inducing RNA silencing or by inhibiting the translation of the target mRNA within the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Among several epigenetic mechanisms, the role of microRNAs in muscle development and myogenesis has been most widely studied in the last decade. MicroRNAs are small, regulatory, non-coding RNA molecules that are mostly located within the cells, although they may also be identified in biological fluids and cell culture media (25). MicroRNAs regulate gene transcription by either inducing RNA silencing or by inhibiting the translation of the target mRNA within the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Since these effects were still observed in vitro, in the absence of paracrine factors, it is likely that intrinsic mechanisms could explain the observed high proliferation and differentiation of SCs. Moresi et al [49,50] have reported epigenetic changes in SCs during the myogenic processes from activation to proliferation and from proliferation to differentiation. They described the activities of the histone methylation, acetylation, and deacetylation that modulate the transcription of specific genes or the role of microRNA enhancing or repressing transcription factors during myogenesis.…”
Section: Mg-specific Factors Have Pathogenic Effects On the Number Anmentioning
confidence: 99%
“…For birds, the number of muscle fibers is determined at birth and postnatal muscle growth is due to hypertrophy or an increase in muscle fiber size, which is accompanied by the proliferative activity of the skeletal muscle satellite cell (SMSC). SMSCs are the kind of pluripotent stem cells that with the ability to proliferate and differentiate could be transformed from a quiescent state into mature muscle fibers under appropriate stimulation [2,3]. Thus, the repair and regeneration of skeletal muscles after injury mainly depends on SMSCs [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…SMSCs are the kind of pluripotent stem cells that with the ability to proliferate and differentiate could be transformed from a quiescent state into mature muscle fibers under appropriate stimulation [2,3]. Thus, the repair and regeneration of skeletal muscles after injury mainly depends on SMSCs [2,4]. It is well-known that growth of SMSCs is regulated by a complex set of biological processes, including many genes [5,6].…”
Section: Introductionmentioning
confidence: 99%